(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Yaroshenko Е. M. Ponomarenko T. B. Intonational nature of music in the context of choreographic art. The concept of intonation as an important conditional form, which is inherit to the contiguous kinds of art-music and choreography, is considered in the article. The relationship between speech intonation, music, dance is traced. Factors of manifestation of intonation in choreography and component parts of choreographic intonation in comparison with the musical one are highlighted. The practical receptions of mastering intonation concepts are provided.